Status of the Novosibirsk terahertz FEL - Bolotin, V.P.; Vinokurov, N.A.; Kayran, D.A.; Knyazev, B.A.; Kolobanov, E.I.; Kotenkov, V.V.; Kubarev, V.V.; Kulipanov, G.N.; Matveenko, A.N.; Medvedev, L.E.; Miginsky, S.V.; Mironenko, L.A.; et al. (Вопросы атомной науки и техники, 2006)
The first stage of Novosibirsk high-power free-electron laser (FEL) was commissioned in 2003. It is based on a normal conducting CW energy recovery linac. Now the FEL provides electromagnetic radiation in the wavelength range of 120…180 micrometers. An average power is 400 W. The minimum measured line width is 0.3%, which is close to the Fourier-transform limit. A user-beamline assembly is in progress, parts of the full-scale machine are manufactured. The latter will operate in the near IR region and provide higher average power